Dravet syndrome: a new causative SCN1A mutation?. Issue 5 (18th March 2017) - Poryo, Martin; Clasen, Oriana; Oehl‐Jaschkowitz, Barbara; Christmann, Alexander; Gortner, Ludwig; Meyer, Sascha
Key Clinical Message: Dravet syndrome is often caused by SCN1A mutations and has a wide variation in clinical appearance. Indication for genetic analysis should be an epileptic encephalopathy or severe clinical course of seizures in infants with episodes of fever before the first year of life. Abstract : Dravet syndrome is often caused by SCN1A mutations and has a wide variation in clinical appearance. Indication for genetic analysis should be an epileptic encephalopathy or severe clinical course of seizures in infants with episodes of fever before the first year of life.